A new species of parasitic isopod (Bopyroidea: Ionidae) infesting burrowing shrimp (Axiidea: Callianassidae) in the tropical eastern Pacific - Hernáez, Patricio; Villegas-Castro, Erick; Boyko, Christopher B. (Zootaxa, 2023)
A new species of parasitic isopod in the genus Ione Latreille, 1818, infesting the branchial chamber of the intertidal burrowing shrimp Neotrypaea tabogensis (Sakai, 2005) is described on the basis of material collected on the Pacific coast of Costa Rica. Diagnostic features of the new species include: (1) body shape of female asymmetrical with slight left distortion, pereon segments distinct; (2) head of female not fused with first pereomere, posterior margin nearly straight; (3) antenna of female composed of five articles; (4) posterior lamella of barbula of female with two tapered lobes on each side; (5) body of male elongated, clearly segmented dorsally; (6) head of male completely separated from the first pereomere; and (7) maxillipeds absent in male. This is the seventh valid species in the genus Ione and the first record of this genus from the tropical eastern Pacific. A key for identification of species of Ione is also provided.